Structural phase transitions in ionic conductor Bi2O3 by temperature dependent XPD and XAS. (May 2016) - Zhu, Yingcai; An, Pengfei; Yu, Meijuan; Marcelli, Augusto; Liu, Yong; Hu, Tiandou; Xu, Wei
Abstract: The superionic behavior of cubic δ-phase Bi2 O3, a metastable phase at high temperature, is of great interests from both scientific and technological perspectives. With the highest ionic conductivity among all known compounds, the δ-phase Bi2 O3 possesses promising applications in solid-oxide fuel cells. Previous investigations pointed out the α to δ- phase transition occurs during the heating process, as supported by the X-ray and Neutron diffraction experiments. Through in situ measurements of the long-range order structure and the local structure by X-ray powder diffraction and X-ray absorption spectroscopy, we investigated the evolution of the structures under different temperatures. Both techniques provided ample evidence that the existence of meta-stable β-phase are crucial for forming the defective fluorite cubic δ phase. Our finding suggested that the phase transition from tetragonal β-phase to δ-phase is an influencing factor for the generation of the oxygen-ion pathways.